Amplification of avian influenza virus circulation along poultry marketing chains in Bangladesh: A controlled field experiment - Lisa Kohnle; Tridip Das; Md. Helal Uddin; Sanjib Chandra Nath; Md. Abu Shoieb Mohsin; Rashed Mahmud; Paritosh Kumar Biswas; Md. Ahasanul Hoque; Dirk Udo Pfeiffer; Guillaume Fournié (Preventive Veterinary Medicine, 2024)

Optical Based Surface Plasmon Resonance Sensor for the Detection of the Various Kind of Cancerous Cell - Shah Ali Rafi; Wahiduzzaman Emon; Ahmed Afif Rafsan; Russel Reza Mahmud; Md. Faysal Nayan; Mahmoud M. A. Eid; Ahmed Nabih Zaki Rashed (Cell Biochemistry and Biophysics, 2024)

Correction to: Mapping of dressed and processed poultry products in Bangladesh: Identifying the food safety risks for policy intervention - Jinnat Ferdous; Helal Uddin; Rashed Mahmud; Mathew Hennessey; Abdullah Al Sattar; Suman Das Gupta; Justine S. Gibson; Robyn Alders; Joerg Henning; Guillaume Fournié; Ahasanul Hoque (Veterinary Research Communications, 2023)

Mapping of dressed and processed poultry products in Bangladesh: Identifying the food safety risks for policy intervention - Jinnat Ferdous; Md Helal Uddin; Rashed Mahmud; Mathew Hennessey; Abdullah Al Sattar; Suman Das Gupta; Justine S. Gibson; Robyn Alders; Joerg Henning; Guillaume Fournié; Md. Ahasanul Hoque (Veterinary Research Communications, 2023)
Bangladesh’s commercial poultry production is growing rapidly, including the commercial processing of poultry. This expansion of poultry processing plants is fueled by the belief that this sub-sector provides safer food and has less food-borne disease risks compared to traditional live bird markets (LBMs). The purpose of this study is to describe Bangladesh’s dressed and processed poultry production and distribution network (PDN), identify what and where quality control occurs, and suggest where improvements could be made. Engaging with PDN for dressed and processed poultry, we used in-depth interviews with key informants to identify the stakeholders involved and their connections with other poultry PDNs. In addition, we mapped out the supply and distribution of dressed and processed poultry and quality control processes occurring throughout the network. We argue that dressed and processed poultry PDNs are closely connected with traditional PDNs such as LBMs, with multiple crossover points between them. Also, there is a lack of consistency in quality control testing and a lack of meat traceability. Consequently, perceptions of dressed and processed poultry being safer than birds from LBMs needs to be treated with caution. Otherwise, unsubstantiated consumer confidence in dressed poultry may inadvertently increase the risk of food-borne diseases from these products.

A Machine Learning-based Approach for Groundwater Mapping - Rashed Uz Zzaman; Sara Nowreen; Irtesam Mahmud Khan; Md. Rajibul Islam; Nabil Ibtehaz; M. Saifur Rahman; Anwar Zahid; Dilruba Farzana; Afroza Sharmin; M. Sohel Rahman (Natural Resources Research, 2022)

Epidemiological assessment of clinical poultry cases through the government veterinary hospital-based passive surveillance system in Bangladesh: a case study - Md. Ashiqur Rahman; Md. Mahbubur Rahman; Md. Sadeque Abdullah; Md. Abu Sayeed; Md. Harun Rashid; Rashed Mahmud; Joseph P. Belgrad; Md. Ahasanul Hoque (Tropical Animal Health and Production, 2019)

Environmental challenges of trans-boundary water resources management: the case of Bangladesh - Mohammed Abdul Baten; Rashed Al Mahmud Titumir (Sustainable Water Resources Management, 2016)